2002
DOI: 10.1046/j.1365-2362.2002.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectin‐P and interleukin‐8 plasma levels in coronary heart disease patients

Abstract: Our findings suggest that soluble form of selectin-P and interleukin-8 may be useful clinical predictors of unstable coronary heart disease. The assessment of the risk for the development of coronary heart disease requires further serial investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…The chemokine IL-8 may be involved in the pathogenesis of atherosclerosis and cardiovascular disease, since in vivo studies have found higher plasma levels of IL-8 in patients with unstable coronary heart disease (2,26). In vitro studies have demonstrated that several inflammatory cells involved in the pathogenesis of atherosclerosis possess IL-8 receptors (28), and IL-8 has been suggested to induce chemotaxis, which may be involved in the formation of atherosclerotic plaque (16,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemokine IL-8 may be involved in the pathogenesis of atherosclerosis and cardiovascular disease, since in vivo studies have found higher plasma levels of IL-8 in patients with unstable coronary heart disease (2,26). In vitro studies have demonstrated that several inflammatory cells involved in the pathogenesis of atherosclerosis possess IL-8 receptors (28), and IL-8 has been suggested to induce chemotaxis, which may be involved in the formation of atherosclerotic plaque (16,21).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its association with a number of different inflammatory processes, IL-8 has also been implicated in the pathogenesis of atherosclerosis (13,21) and coronary heart disease (26). Plasma levels of IL-8 have been found to be significantly increased in patients with both type 1 and type 2 diabetes compared with healthy subjects (9,29).…”
mentioning
confidence: 99%
“…29,30 Enhanced IL-8 production was observed in human abdominal aortic aneurysms, 31 and IL-8 plasma levels were in increased coronary heart disease patients. 32 In addition, IL-8 was significantly increased in infarct-related coronary artery thrombi and atherosclerotic plaque specimens obtained with a transluminal extraction catheter from cases of acute myocardial infarction. 33 Because release of IL-8 and MCP-1 was also observed in oxLDL incubated macrophages, these cytokines may play an important role in the host response to inflammation 2 within the vessel wall and we therefore analyzed them as model cytokines.…”
Section: Dje N'guessan Et Al Statins Control Oxldl-related Histone Momentioning
confidence: 95%
“…Thus, MCP-1 appears to play a crucial role at multiple stages of atherosclerosis, and is a potent alternative biomarker and a possible therapeutic target (69). Similarly to the above, Romuk et al evaluated levels of CXC chemokine IL-8 and demonstrated significantly higher levels of IL-8 in unstable coronary heart disease patients in comparison to stable coronary heart disease patients and controls, concluding that a soluble form of IL-8 may be a useful clinical predictor of unstable coronary heart disease (70).…”
Section: Discussionmentioning
confidence: 99%